2018
DOI: 10.1093/geront/gny031
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of the Relocation of Patients With Dementia: A Scoping Review to Inform Medical and Policy Decision-Making

Abstract: The outcomes of the study suggest definite evidence for the negative effects of relocation of the older adults. This research aims to be used as the support of the legal and medical decisions of relocation of patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
1
18
1
Order By: Relevance
“…Cognitive decline and dementia progression can lead to numerous care transitions, which are associated with declines in health and quality of life for people living with dementia (PLWD) and their caregivers ( Chyr et al, 2020 ; Ryman et al, 2018 ). Older adults and their families may seek advice from their physicians as they decide whether to move into an AL/RC ( Alzheimer’s Association, 2020 ; Chen et al, 2008 ; Reinardy & Kane, 2003 ).…”
Section: Al/rc Settings Their Residents and Staffmentioning
confidence: 99%
“…Cognitive decline and dementia progression can lead to numerous care transitions, which are associated with declines in health and quality of life for people living with dementia (PLWD) and their caregivers ( Chyr et al, 2020 ; Ryman et al, 2018 ). Older adults and their families may seek advice from their physicians as they decide whether to move into an AL/RC ( Alzheimer’s Association, 2020 ; Chen et al, 2008 ; Reinardy & Kane, 2003 ).…”
Section: Al/rc Settings Their Residents and Staffmentioning
confidence: 99%
“…However, older adults are often hesitant and reluctant toward relocation and prefer to age at home. This preference is defendable, even in older adults with dementia, because recent research shows the negative effects of relocation on well-being in this group ( Ryman et al., 2018 ). Although it is clear that living at home as long as possible is desirable for many reasons, the implementation can be challenging.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Studies have shown that when the ideal and actual living arrangements of the older adults are the same, it has a positive and significant impact on their overall life and satisfaction [17]. Being newly admitted to a LTCF forces older adults with disabilities to leave their homes and face a completely new life pattern, which is a major life change that requires attention [5,8,10,18,19]. In Taiwan's traditional concept, home is the most anticipated residence for the older adults.…”
Section: Introductionmentioning
confidence: 99%